A regra matriz do direito ao crédito na não-cumulatividade do ICMS - Balanin, Rafael (2014)
The objective of this work is to identify whether the Non Cumulative should be considered as true Constitutional Rule and not as Principle, created along with the authorization to institute the Brazilian State VAT ( ICMS ). Apart the consideration if Non Cumulative should be framed as a Principle or Rule, we seek to demonstrate that VAT cannot exist without attending it. In view of this, we will seek to better identify how the Rule of Non Cumulative establishes the use of ICMS credit on the tax owed in the previous step. What we seek is to confirm that, even if such tax has not been paid by the supplier in the previous step of the circulation chain, by any circumstance, once held the ICMS the right to use the credit shall be ensured. Therefore, as the Federal Constitution does not require the payment of ICMS in the previous step to enforce the Rule of Non Cumulative , once that the incidence of taxation occur (due to the effective delivery of goods) the purchaser is entitled to the use of credits from the subsequent operation. In view of this, we believe that requiring reversal of ICMS credits arising from any non-payment or underpayment of tax in the previous step violates the Rule of Non Cumulative of VAT and, therefore, is unconstitutional